Comparative Study between Degradation Analysis and First Order Reliability Method for Assessing Piping Reliability for Risk-Based Inspection - Mokhtar, Ainul Akmar (2009)
Abstract—Piping systems in refineries and petrochemical plants are exposed to corrosive environment causing various types of degradation mechanisms. One of the damage mechanisms experienced is gradual wall thinning that causes the pipe to leak. Since the piping systems carry hydrocarbons or other process fluids, the presence of small leak may lead to a hazardous situation. Therefore, proper inspection and maintenance of these systems is essential for maintaining a safe and continuous operation. Risk-based inspection (RBI) strategy has been adopted to establish the inspection strategy for piping systems where the strategy is based on risk calculated. Risk is defined as the product of the probability of failure and its consequences of failure. Assessing the failure probability for piping systems in RBI approach typically follows the guideline by American Petroleum Institute (API 581) where the method is deterministic. This study explores the available probabilistic analysis techniques in estimating the piping failure probability, namely, degradation analysis and first-order reliability method (FORM). The objective of this paper is to estimate the pipes failure probability using these two techniques where both models require different input data. Degradation analysis only uses the pipe wall thickness data that are usually being collected during inspection for pipes subject to wall thinning. Conversely, FORM model requires data on material properties and physical geometric of the piping system to estimate the failure probability. The failure probability estimated by these two techniques are then compared and discussed. The results showed that the degradation analysis is more conservative compared to FORM.